2021
DOI: 10.1016/j.socscimed.2021.113743
|View full text |Cite
|
Sign up to set email alerts
|

A spectrum of (Dis)Belief: Coronavirus frames in a rural midwestern town in the United States

Abstract: Community responses to the SARS-CoV-2, or “coronavirus” outbreaks of 2020 reveal a great deal about society. In the absence of government mandates, debates over issues such as mask mandates and social distancing activated conflicting moral beliefs, dividing communities. Policy scholars argue that such controversies represent fundamental frame conflicts, which arise from incommensurable worldviews, such as contested notions of “liberty” versus “equity”. This article investigates frames people constructed to mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Considering COVID-19 as a social construct, rather than simply a biological entity, provides a rare account of the virus diffusion mechanisms involved in human action and interaction. Our research contributes insight into the frame or category dynamics that are especially helpful for promoting understanding of how health crises evolve over time ( Dhanani and Franz, 2021 ; Koon et al, 2021 ; Ogbodo et al, 2020 ). We identify the socio-cognitive frame as a key mechanism through which the COVID-19 is perceived, interpreted, and evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering COVID-19 as a social construct, rather than simply a biological entity, provides a rare account of the virus diffusion mechanisms involved in human action and interaction. Our research contributes insight into the frame or category dynamics that are especially helpful for promoting understanding of how health crises evolve over time ( Dhanani and Franz, 2021 ; Koon et al, 2021 ; Ogbodo et al, 2020 ). We identify the socio-cognitive frame as a key mechanism through which the COVID-19 is perceived, interpreted, and evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that a virus that causes a global pandemic can be seen as both biologically conditioned and socially constitutive. The spread of COVID-19 has opened the way to issue framing that involves the interpretative work and discursive construction of various actors ( Bolsen et al, 2020 ; Dhanani and Franz, 2021 ; Koon et al, 2021 ). To biologists and scientists, the virus consists of a single-stranded RNA genome enveloped by a nucleocapsid (protein shell) of helical symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…As others have also pointed out, a distinction between politics and partisanship must be made (Grossman et al, 2020;Youde, 2020), and it is at the level of partisanship that symbols and scripts become particularly powerful as a means of divisive communication and influence. The absence of clear national leadership and policymaking on key issues like mask-wearing has created a vacuum that quickly gets filled by cultural squabbles and value-based disputes (Koon et al, 2021). Shaming, blaming, and stigmatisation thrive in these contexts, particularly where clear and non-contradictory evidence fails to be communicated by national leaders.…”
Section: Discussionmentioning
confidence: 99%
“…Busy weekends, such as Independence Day celebrations, have attracted a half-million visitors. We interviewed mostly year-round residents and some summer residents from June to September in 2020, quickly assembling the project amidst the biggest outbreak in the town, as cases hiked from eight to 200 within one month (see Koon et al, 2021). We expanded the study after the initial outbreak to better understand people with different political affiliations, income, occupations, and beliefs.…”
Section: Methods and Contextmentioning
confidence: 99%
“…In an experimental study, Dhanani and Franz (2021) showed how framings that spoke about the origins of the coronavirus in China induced more xenophobic attitudes in respondents. Koon et al (2021) identified four types of frames articulated in the narratives of citizens of a small US town in the summer of 2020 (concern, crisis, constraint, and conspiracy frames), revealing highly conflicting perspectives strongly associated with demographics and divergent political affiliations.…”
Section: What Is "This" a Case Of? Process As Narrativementioning
confidence: 99%